Guide to General Histology and Microscopic Anatomy - Vaňhara, Petr (Masaryk University Press, 2020)
This Guide to General Histology and Microscopic Anatomy is intended to provide the effective support particularly for students of Medicine or Life sciences enrolled to the courses provided by the Department of Histology and Embryology at the Faculty of Medicine, Masaryk University. The Guide includes original, high-quality microphotographs and electronograms, annotated with contemporary terminology on histology and microscopic anatomy of tissues and organs. The Guide, however, does not aim to substitute a histology textbook or microscopy anatomy atlas and avoids detailed textual explanations that can be found elsewhere. The Guide rather contributes to better understanding, follow-up and self-orientation in practical lessons, lectures and seminars of the Department. The authors believe that this Guide will help to unravel fine patterns of human microscopic structures within their amazing complexity and diversity.